An Alternative Impression Technique for Fabrication of Feeding Appliance for an Infant with Cleft Palate: A Clinical Report - Dhital, S; Mathema, S R.B.; Maskey, B (Journal of Nepalese Prosthodontic Society, 2020)
Cleft lip and palate is the most common congenital defect of the orofacial region, which results in difficulty in feeding, deglutition, and speech. Before the surgical intervention, a feeding appliance is used to restore the palatal cleft and aid in feeding an infant. The impression procedure during the fabrication of a feeding appliance is a crucial step and selection of impression tray and impression material is a challenging task. This article attempts to briefly describe an alternative technique for making impressions in infants with cleft palate.